Ecology and morphological variations in wings of Phlebotomus ariasi (Diptera: Psychodidae) in the region of Roquedur (Gard, France): a geometric morphometrics approach. Issue 1 (December 2016) - Prudhomme, Jorian; Cassan, Cécile; Hide, Mallorie; Toty, Céline; Rahola, Nil; Vergnes, Baptiste; Dujardin, Jean-Pierre; Alten, Bulent; Sereno, Denis; Bañuls, Anne-Laure
Abstract Background Phlebotomus ariasi Tonnoir, 1921, is the predominant sand fly species in the Cevennes region and a proven vector ofLeishmania infantum, which is the main pathogen of visceral and canine leishmaniasis in the south of France. Even if this species is widely present in Western Mediterranean countries, its biology and ecology remain poorly known. The main goals of this work are to investigate the phenotypic variation ofP. ariasi at a local scale in a region characterized by climatic and environmental fluctuations, and to determine if slope and altitude could affect the sand fly phenotypes. Results Sand flies were captured along a 14 km-long transect in 2011 from May to October. At the same time, environmental data such as altitude and slope were also collected. Morphological analysis ofP. ariasi wings was performed by a geometric morphometrics approach. We found morphological variation among local populations ofP. ariasi . Strong shape and size variations were observed in the course of the season (particularly in June and July) for both genders. During June, we highlighted differences in wing phenotypes according to altitude for both sexes and to slope and station for females. Conclusions The phenotypic variations observed inP. ariasi along the studied transect indicated these populations are subjected to environmental pressures. Nevertheless, it seems that sand flies are more sensitive to extrinsic factors in June and July, suggesting a phenotypic plasticity.